Argument Property for Certain Analytic Functions - Qing Yang; Jin-Lin Liu (Abstract and Applied Analysis)
Let P be the class of functions p(z) of the form ∑𝑝(𝑧)=1+∞𝑛=1𝑐𝑛𝑧𝑛 which are analytic in the open unit disk 𝑈={𝑧∶|𝑧|<1}. The object of the present paper is to derive certain argument inequalities of analytic functions p(z) in P.